Endothelial glycocalyx—the battleground for complications of sepsis and kidney injury. Issue 2 (23rd May 2017) - Song, Jong Wook; Zullo, Joseph; Lipphardt, Mark; Dragovich, Matthew; Zhang, Frank X; Fu, Bingmei; Goligorsky, Michael S
Abstract: After briefly discussing endothelial glycocalyx and its role in vascular physiology and renal disease, this overview focuses on its degradation very early in the course of microbial sepsis. We describe our recently proposed mechanism for glycocalyx degradation induced by exocytosis of lysosome-related organelles and release of their cargo. Notably, an intermediate in nitric oxide synthesis, NG-hydroxy-l-arginine, shows efficacy in curtailing exocytosis of these organelles and improvement in animal survival. These data not only depict a novel mechanism responsible for very early glycocalyx degradation, but may also outline a potential preventive therapy. The second issue discussed in this article is related to the therapeutic acceleration of restoration of already degraded endothelial glycocalyx. Here, using as an example our recent findings obtained with sulodexide, we illustrate the importance of the expedited repair of degraded endothelial glycocalyx for the survival of animals with severe sepsis. These two focal points of the review on glycocalyx may not only have broader disease applicability, but they may also provide additional evidence to buttress the idea of the importance of endothelial glycocalyx and its maintenance and repair in the prevention and treatment of an array of renal and nonrenal diseases.